Improving Students’ Speaking Ability Using Vlog on Tik-Tok for The Eleventh Grade of SMA Negeri 13 Maluku Barat Daya - Komandely, Daniel; Anaktototy, Karolis; Tiwery, Dian (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2023)
The objective of this study was to improve students speaking abilities of the eleven grade students at SMA NEGERI 13 MBD, which consisted to 24 students. This research used Classroom Action Research. The steps were preliminary study, planning, implementation, evaluation and reflection. The data were collected through pre-test and post-test, teacher observation and the students’ feedback through questionnaire. This study occurred over two cycles and took over of nine meetings. The data showed that the first cycle was not successful because it only achieved 36. 27 % success rate. Therefore, it was then continued to second cycle and there was an increase to 84.1%. Based on the outcomes of the use of vlog it proven to have a significant positive impact on students’ speaking proficiency especially in four main aspects, performance, pronunciation, grammar and vocabulary. Through vlog the students were able to deliver their effort to make a video in an innovative and imaginative way, giving them the courage to express themselves.